Regulation of a delicate problem in patients with rectal diseases - V. V. Skvortsov; A. A. Eremenko; N. V. Eremenko (Амбулаторная хирургия, 2022)
This paper highlights the problem of chronic constipation, their epidemiology, etiology, clinical features in some concomitant diseases, diagnostics and approaches to therapy with a focus on sodium picosulfate preparations. Based on several scientific papers, an analysis of a group of sodium picosulfate preparations was performed, indications, dosage, efficacy and possible side effects were considered. The paper also provides a clinical example of managing a patient with chronic constipation. Who received therapy with sodium picosulfate. Constipation is a violation of the act of defecation less than 3 times a week or more than three days. At the same time, it is possible to say about chronic constipation if such symptoms persist for 6 months. To date, the discussion about constipation as a nosological unit continues. The study of the epidemiology of constipation in various scientific sources indicates the wide spread of this disease. The diagnosis of “Constipation” is based on the Rome Criteria IV adopted in 2016. By origin, constipation can be primary and secondary, and among the factors provoking them are not only gastroenterological diseases, but diseases of other organ systems, as well as environmental factors and the intake of certain groups of medicines. Therapy of chronic constipation is carried out both medicamentally and non-medicamentally (surgical methods today have no proven effectiveness). The analysis of sodium picosulfate preparations proved their effectiveness and safety, which was also noted in our clinical case.